CROSS-LINGUISTIC INFLUENCE IN L1 LANGUAGE ATTRITION AND SIMULTANEOUS ACQUISITION: EVIDENCE FROM ITALIAN/ TURKISH BILINGUALS - Ergun, Anna Lia Proietti (UNIV CONCEPCION, FAC HUMANIDADES ARTE, 2021)
The present study reports data from a 40-item acceptability judgment task in Italian on the interpretation of backward anaphora in complex sentences in which three groups participated. The groups included bilingual Italian native speakers highly proficient in Turkish as a second language (L2), and Turkish and Italian simultaneous bilingual (2L1) children and monolingual native Italian speakers as a control group. In the 40-item acceptability judgment task in Italian, they were asked the degree of acceptability of sentences introduced by short stories suggesting coreference or disjoint reading of the overt or null pronoun. It was assumed that Italian and Turkish languages do not differ with respect to the antecedent biases of null and overt subject pronouns in the contexts under investigation, except for anaphoric pronoun kendi that when it is used as the third person singular or plural, always expressing anaphoric references with the subject in the matrix sentence. The findings revealed a significant difference in the monolingual group regarding the null pronoun when preceded by a quantifier. This is discussed as evidence for the cross-linguistic influence at the syntax-discourse interface in 2L1 acquisition in children and in L1 attrition in language with similar parametric settings and for the fact that quality and quantity of input in the native or minority language can significantly diminish the effect.
Keywords: cross-linguistic influence; early bilingualism; attrition; Turkish; Italian; L2 ACQUISITION; DISCOURSE; SYNTAX; GENDER; FRENCH; INPUT; AGE; Linguistics